EMPOWERING TEACHERS TO INCREASE A QUALITY OF INDONESIAN’S EDUCATION - HENNY YULIA (Universitas Jambi, 2017)
Quality of education is greatly influenced by the quality of teachers and students. To provide high quality of education, the government should commit to ensure that every student has the opportunity to learn from qualified and inspiring teachers. In recognition of the importance of qualified teachers, policy initiatives that push toward getting smarter people into the teacher workforce have been introduced. This paper provides an overview of the government’s strategies, teacher training and certification, UKG, MGMP, and KKG, to improve the quality of teachers in Indonesia. The idea is simple: if we can insist on better prepared and more able teachers, teacher quality will necessarily rise and student performance will respond.